Detection and molecular epidemiology of ciprofloxacin-resistant Neisseria gonorrhoeae, using a real-time polymerase chain reaction (PCR) - Magooa, Mahlape Precious (My University, 2011)
Emergence and spread of resistance to ciprofloxacin among Neisseria gonorrhoeae strains has reduced the options of effective treatment for gonococcal infections and has become a concern worldwide. Up until 2008, ciprofloxacin was recommended first-line therapy for treatment of presumptive N. gonorrhoeae infections in South Africa. At the time this MSc project was conceived, ciprofloxacin was still used as first-line therapy for presumptive gonococcal infections. A real-time polymerase chain reaction (PCR) assay was used to detect ciprofloxacin-resistant N. gonorrhoeae in DNA extracted from non-invasive urine samples collected as part of the national microbiological surveillance (NMS) programme during 2006-2007. The molecular epidemiology of ciprofloxacinresistant Neisseria gonorrhoeae was investigated by sequencing the quinolone resistance determining regions (QRDR) of the gyrA and parC genes of N. gonorrhoeae and performing N. gonorrhoeae multi-antigen sequence typing (NGMAST). As part of the NMS program for sexually transmitted infections (STIs) urine and urethral swabs were collected from men presenting with urethral discharge at primary health care clinics in Johannesburg (Gauteng), Cape Town (Western Cape) and Kimberley (Northern Cape). Urine samples and cultured N. gonorrhoeae isolates from 2006-2007 were stored at -700C and available for this study. Gonococci, previously isolated from urethral swabs, were subcultured directly onto New York City media. Isolate identity was re-confirmed by typical colony morphology and biochemical tests. Urine samples from Johannesburg were tested in order to develop the real-time PCR protocol. Subsequently, paired urethral swab DNA and N. gonorrhoeae cultures were tested from NMS patients recruited in Kimberley and Cape Town. Where possible, the PCR assay results were compared with paired antibiotic susceptibility data for ciprofloxacin. Quinolone resistance determining regions (QRDR) for gyrA and parC were screened for known point mutations associated with resistance to ciprofloxacin. Detection of mutations by the real-time PCR assay generally agreed with the phenotype of either decreased susceptibility or resistance to ciprofloxacin. All ciprofloxacin resistant gonococcal isolates had the same gyrA and parC mutations, which initially suggested that quinolone resistant N. gonorrhoeae (QRNG) in Kimberley, Cape Town and Johannesburg, may be attributed to the spread of a single clone. The use of a more discriminatory typing scheme, Neisseria gonorrhoeae Multi-Antigen Sequence Typing (NG-MAST) genotyping, revealed that ciprofloxacin resistant gonococcal isolates in Johannesburg and Cape Town were heterogeneous, with sequence type (ST) 217 being most prevalent in both cities (5/16, Johannesburg; 7/11, Cape Town). In contrast, all eight QRNG isolates from Kimberley were typed as ST 533. The use of molecular methods allowed ciprofloxacin antimicrobial susceptibility determination by PCR in non-invasive specimens. This is useful in situations where bacterial cultures are unavailable or die before antimicrobial susceptibility testing can be performed. Molecular assays to detect ciprofloxacin resistance may guide physicians as to the most ideal antimicrobial combinations for individual patient treatment. As a result of emerging widespread resistance gonococci to ciprofloxacin, in 2008, the Department of Health recommended that ciprofloxacin be removed as a first line therapy in the South African national sexually transmitted infections treatment guidelines for treatment of urethritis, cervicitis and their complications. Although ciprofloxacin is no longer used as a first-line therapy to treat gonorrhoea within our country, it may still be used in cases of severe penicillin allergy or as part of multi-drug therapy for gonococcal infections in the future. The ability to detect ciprofloxacin resistance by real-time PCR will be a useful technique in such situations.
MSc (Med), Clinical Microbiology and Infectious Diseases, Faculty of Health Sciences, University of the Witwaterstrand
Keywords: gonorrhea; drug resistance; ciprofloxacin; detection; polymerase chain reaction; PCR